2019
DOI: 10.1037/xlm0000538
|View full text |Cite
|
Sign up to set email alerts
|

Feature highlighting enhances learning of a complex natural-science category.

Abstract: Learning naturalistic categories, which tend to have fuzzy boundaries and vary on many dimensions, can often be harder than learning well defined categories. One method for facilitating the category learning of naturalistic stimuli may be to provide explicit feature descriptions that highlight the characteristic features of each category. Although this method is commonly used in textbooks and classrooms, theoretically it remains uncertain whether feature descriptions should advantage learning complex natural-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 52 publications
2
53
2
Order By: Relevance
“…Considering the most effective methods of organising the training of air traffic controllers, he concludes that in many cases, teaching using visual aids is more effective than using verbal messages (Holt, 1964). Modern research shares the importance of visual images in learning (Miyatsu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the most effective methods of organising the training of air traffic controllers, he concludes that in many cases, teaching using visual aids is more effective than using verbal messages (Holt, 1964). Modern research shares the importance of visual images in learning (Miyatsu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Much other research has also pursued techniques for effectively teaching categories at a single level of a hierarchy. Such techniques include ones that manipulate the presentation sequences of training instances from contrasting categories (e.g., Carvalho & Goldstone, 2014; Eglington & Kang, 2017; Kornell & Bjork, 2008; Mathy & Feldman, 2016); the order in which hard versus easy instances are presented (e.g., Pashler & Mozer, 2013); the size of the sets of training instances and which specific training instances to use (e.g., Nosofsky et al, 2018, 2019; Wahlheim et al, 2012); and the use of explicit coaching such as visual highlighting of diagnostic features (Miyatsu, Gouravajhala, Nosofsky, & McDaniel, 2019). Combining these techniques with variants of the presently proposed two-stage response procedure might yield even better learning of hierarchically organized science categories.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another approach that is emerging in the basic cognitive research is specifying the types of explicit Bcoaching^that can enhance category learning. One type of coaching involves providing learners with explicit information about characteristic features or rules that are diagnostic for each category (e.g., Miyatsu, Gouravajhala, Nosofsky, & McDaniel, 2018;Pashler & Lovelett, 2017). For instance, Miyatsu et al (2018) found that highlighting characteristic features of particular rock categories during training (by circling and describing specific features on the image of each training token) produced more accurate generalization to new instances than when learners were not provided such highlighting.…”
Section: Number and Variability Of Training Instancesmentioning
confidence: 99%
“…One type of coaching involves providing learners with explicit information about characteristic features or rules that are diagnostic for each category (e.g., Miyatsu, Gouravajhala, Nosofsky, & McDaniel, 2018;Pashler & Lovelett, 2017). For instance, Miyatsu et al (2018) found that highlighting characteristic features of particular rock categories during training (by circling and describing specific features on the image of each training token) produced more accurate generalization to new instances than when learners were not provided such highlighting. Likewise, Eglington and Kang (2017) found that, in crossexperiment comparisons, explicit highlighting of diagnostic features improved learning and generalization in the domain of chemistry categories.…”
Section: Number and Variability Of Training Instancesmentioning
confidence: 99%